2017
DOI: 10.1103/physrevb.96.115306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of geometric nonlinearity in a nonprismatic and heterogeneous microbeam resonator

Abstract: Implementation of geometric nonlinearity in micro-electro-mechanical system (MEMS) resonators offers a flexible and efficient design to overcome the limitations of linear MEMS by utilizing beneficial nonlinear characteristics not attainable in a linear setting. Integration of nonlinear coupling elements into an otherwise purely linear microcantilever is one promising way to intentionally realize geometric nonlinearity. Here, we demonstrate that a nonlinear, heterogeneous micro-resonator system, consisting of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Previous studies [13,14,33] have reported a tuning effect of the electrical nonlinearity and mechanical nonlinearity in silicon-based MEMS by applying dc bias. The electrical nonlinearity is typically produced by electrostatic force [34,35] in plate capacitor, and the mechanical nonlinearity is produced by the intrinsic material and geometric nonlinearity [36,37]. These previous works have reported that the current handling in quartz or silicon MEMS resonators can be explained by the nonlinear A-f dependence effect.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [13,14,33] have reported a tuning effect of the electrical nonlinearity and mechanical nonlinearity in silicon-based MEMS by applying dc bias. The electrical nonlinearity is typically produced by electrostatic force [34,35] in plate capacitor, and the mechanical nonlinearity is produced by the intrinsic material and geometric nonlinearity [36,37]. These previous works have reported that the current handling in quartz or silicon MEMS resonators can be explained by the nonlinear A-f dependence effect.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, changes in the stiffness of the MEMS structure will lead to nonlinearity, and these changes of stiffness can be attained by using certain materials, particularly piezoelectric ones [ 28 ]. These changes in stiffness can also be induced by the use of geometrical nonlinearity, as MEMS devices generally undergo relatively large deformation [ 32 ]. This geometrical nonlinearity can be caused by a wide range of factors, such as large deflections or rotations, initial stresses, or load stiffening.…”
Section: Methodsmentioning
confidence: 99%
“…In this design, the axial stiffness of the attached polymer component is~40 times lower than that of the Si microbeam. Hence, when the system oscillates, the freestanding polymer component is axially stretched, resulting in geometric nonlinearity 52 . The dimensions of the structural components were deliberately chosen to produce the desired 1:2 ratio between the second and third mode frequencies: the length (L), width (b), and thickness (h) of the silicon microbeam (subscript 1) and polymer coupling (subscript 2) are…”
Section: Experimental Characterization Of Internal Resonancementioning
confidence: 99%
“…The thermomechanical response measured by a laser Doppler vibrometer (LDV) showed that the first three linearized mode frequencies were f 1 ffi 42 kHz; f 2 ffi 107 kHz, and f 3 ffi 214 kHz and that the second and third mode frequency values satisfied the 1:2 relation of commensurability. The strong geometric nonlinearity in the heterogeneous nonprismatic design 52 , combined with the 1:2 ratio between the mode frequencies, triggers the IR in the dynamic response. This outcome implies that the second and third modal responses can be internally coupled if the system is driven hard enough into the nonlinear regime.…”
Section: Experimental Characterization Of Internal Resonancementioning
confidence: 99%